Design and cold simulation of a metal PBG cavity for sub-millimeter wave gyrotron - Singh R.K.; Thottappan M. (My University, 2025)
In this paper, the design and simulation of a metal photonic band gap (PBG) cavity is presented for sub-millimeter wave gyrotrons. A triangular unit cell of a regular metal PBG structure has been investigated using an ADI-FDTD numerical algorithm. The dispersion of this unit cell is plotted in order to study the nature of propagation of electromagnetic (EM) wave. The metal PBG cavity is realized by making a defect in the 2-D periodic triangular structure. The designed PBG cavity is modeled in 'CST Microwave Studio' for observing the mode purity and its propagation and reflection behaviors. The transient analysis of the cavity predicted its return loss as ∼ 32.45 dB and its quality factor as 7830 at 250 GHz. © 2017 IEEE.